MEDIA REPRESENTATION OF WOMEN’S WITH RESPECT TO OTT PLATFORMS IN INDIA - Ghildiyal, Ankit; Jayaswal, Sudhashu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the rapid advancement of ICT over the past 10 years, the proliferation of over-the-top (OTT) platforms has given Indian viewers access to a vast universe of information. With the help of these web-based streaming services, viewers can make custom movies and TV shows. Platforms used by Over the Top (OTT) to deliver streaming content to users via the Internet. OTT streaming platforms like Zee5, Hotstar, Netflix, Amazon Prime, Alt Balaji, and others are readily accessible in India with the use of the internet on smartphones via applications, smart TVs via websites, and personal desktops or laptops via websites. In the last few years, there has been an increase in the representation of women on OTT stages. These stages are now hosting a number of successful shows and films that demonstrate how much the audience enjoys female-driven narrative. Exceptional female Netflix viewers increased to 40% in 2019 from 26% in 2018, according to data from Comscore. This year, a female producer or director was involved in almost half of the Netflix films that were released in India. The situation in India reflects a global trend where more women are involved in the creation of streaming content specifically for women. The study has a particular focused in the representation of women, difficulties, and government regulations in the Indian OTT platforms.